(untitled) (PRÁXIS EM SAÚDE, 2025)
Palliative care constitutes an approach that seeks to provide comprehensive assistance to people in the final stages of life, through humanized care that values well-being and ensures conditions for a dignified and comfortable experience. In this sense, the objective of this study is to discuss how palliative care contributes to the guarantee of human dignity for patients facing the end of life, highlighting its importance in promoting a life with quality. To achieve this, an integrative literature review was conducted, through the reading and analysis of studies that address this topic to gain a broader understanding of the subject. It is concluded that the palliative approach is fundamental for the humanization of care for hospitalized patients, as it offers assistance that goes beyond physical care to embrace comprehensive care.